The Importance in Developing Professional Skills at the Workplace - Adisty Shabrina Nurqamarani (LPPM University 17 Agustus 1945 Samarinda, 2017)
This article contains an exploratory study of professional skills in global context. The aim of the study is to elaborate the importance of developing professional skills in the workplace as well as to explore the drivers of professional skills development. The methodology of study is based on literature review. The study examines the demand for professional skills development in global contexts and factor that shaping the demands using theoretical evidence. The result of the study showed that dynamic global environment has influenced the demand for professional skills, in terms of recruiting more skilled worker and employees who are highly initiative to develop their professional skill. Thus, it is necessary for individual and company to develop professional skills.